Changing Concepts of the Boundaries within ODL - Hodgson, Vivien (Proceedings of the International Conference on Networked Learning, 2000)
This paper takes as its starting point the work of such authors as John Coffey (1977), who distinguishes between the removal of educational and/or administrative constraints to learning, and Richard Boot and Vivien Hodgson, (1987) who describe two main orientations to open learning. a dissemination orientation and a development orientation. The assumption is that like most conventional education ODL has., until now, taken a primarily dissemination orientation and has been concerned with the removal of mostly the administrative constraints that learners are often confronted with in conventional classroom based educational provision. It is, however, recognised that in recent times there has been a growing interest in so called constructionist approaches to education, which, together with the development of ever more information and media rich learning environments has led to a greater concern in removing educational as well as administrative constraints to learning. This has led to a much greater examination of the role of both teachers and learners, as well as examining in more detail the boundaries created due to such aspects as cultural and language differences, existing educational traditions and from gender and racial biases in educational practices. The paper examines the work of primarily three ODL Socrates projects that will present as part of a focus group on changing concepts of the boundaries within ODL.